2008
DOI: 10.1002/ejoc.200700975
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of “Trioxaquantel”® Derivatives as Potential New Antischistosomal Drugs

Abstract: Over the past 20 years, praziquantel, a pyrazinoisoquinoline derivative, has become the mainstay for morbidity control of human and animal schistosomiasis. From early in their lives in vertebrate hosts, schistosomes ingest hemoglobin and aggregate the released heme as a dark pigment very similar to the hemozoin produced by Plasmodium in malaria infection. The antimalarial artemisinin derivatives have real, though low, schistosomicide activity. Because of the complementarity of the two drug classes – praziquant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 56 publications
2
38
0
1
Order By: Relevance
“…15,16,24,31,32 The optically pure four (η 6 -PZQ)Cr(CO) 3 derivatives were prepared using R-PZQ and S-PZQ following a procedure reported for synthesis of 1 and 2. 15 The purities of compounds ( 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 with an electrospray ionization source.…”
Section: Praziquanamine Trans-4-pzq-oh and Cis-4-pzq-oh R-pzq And Smentioning
confidence: 99%
“…15,16,24,31,32 The optically pure four (η 6 -PZQ)Cr(CO) 3 derivatives were prepared using R-PZQ and S-PZQ following a procedure reported for synthesis of 1 and 2. 15 The purities of compounds ( 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 with an electrospray ionization source.…”
Section: Praziquanamine Trans-4-pzq-oh and Cis-4-pzq-oh R-pzq And Smentioning
confidence: 99%
“…Robert, Meunier et al disclosed the synthesis and biological evaluation of trioxaquantels which are hybrid molecules made of the 1,2,4-trioxane unit of the antimalarial drug artemisin and the pyrazinoisoquinoline moiety of PZQ. 10 Only one of their compounds was found have a moderate anti-parasitic activity. Recently, Domling et al reported the synthesis of PZQ derivatives using a Ugi 4-component reaction 11 and they observed that a few of their analogues were as active as the parent drug PZQ.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, praziquanamine (1) was prepared following a previously reported literature procedure. 10 Biological Evaluation. An ideal antiparasitic agent is supposed to kill selectively the parasites without, or to a significantly less extend, being harmful to the host.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that antimalarial artemisinin derivatives, which are heme-alkylating agents (14), and synthetic trioxolanes also display significant activity against several Schistosoma species (18, 19). Our first attempt to obtain antischistosomal drugs based on new hybrid compounds, trioxaquantels, which are based on 1,2,4-trioxanes linked to praziquantel, did not provide the expected activity (9). For these reasons, we decided to evaluate the activities of trioxaquines against Schistosoma mansoni (Fig.…”
mentioning
confidence: 99%